Dielectric and thermal studies of segmental dynamics in silica/PDMS and silica/titania/PDMS nanocomposites. Issue 23 (7th July 2014) - Sulym, Iryna; Klonos, Panagiotis; Borysenko, Mykola; Pissis, Polycarpos; Gun'ko, Vladimir M.
ABSTRACT Effects of silica and silica/titania nanoparticles on glass transition and segmental dynamics of poly(dimethylsiloxane) (PDMS) were studied for composites of a core–shell type using differential scanning calorimetry, thermally stimulated depolarization current, and dielectric relaxation spectroscopy techniques. Strong interactions between the filler and the polymer suppress crystallinity (Tc, Xc) and affect significantly the evolution of the glass transition in the nanocomposites. The segmental relaxation associated with the glass transition consists of three contributions, arising, in the order of decreasing mobility, from the bulk (unaffected) amorphous polymer fraction (α relaxation), from polymer chains restricted between condensed crystal regions (αc relaxation), and from the semi‐bound polymers in an interfacial layer with strongly reduced mobility due to interactions with surface hydroxyls of silica and silica/titania nanoparticles (α′ relaxation). The evolution of surface affected CH3 groups, as well as the degree of interaction of PDMS molecules with surface hydroxyl groups as a function of treatment temperature, was assessed by Fourier transform infrared spectroscopy, thermogravimetry and differential thermal analysis. The effectiveness of silica/PDMS and silica/titania/PDMS nanocomposites as hydrophobic coatings was investigated by static contact angle measurements. It was shown that the presence of titania nanoparticles and adsorbed PDMS promotes the hydrophobic properties of the PDMS coating after treatment in the 80–650°C range. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41154.